PENGARUH MODEL PEMBELAJARAN GROUP INVESTIGATION TERHADAP HASIL BELAJAR BIOLOGI DITINJAU DARI TINGKAT KREATIVITAS SISWA KELAS X SMAN 2 KARANGANYAR - Richvana, Aulia; Dwiastuti, Sri; Prayitno, Baskoro Adi (Pendidikan Biologi, 2012)
ABSTRACT - This research  aimed  to know,  (1)  The existence of significant influence?s  Group Investigation  model towards the results study of Biology class X SMAN 2 Karanganyar, (2) The existence of significant influence?s creativity level towards the results study of Biology students in class X SMAN 2 Karanganyar, (3) The  interaction of significant influence?s between Group Investigation  model and creativity level towards the results study of Biology students in class X SMAN 2 Karanganyar. This research is Quasi Experimental Research. Subject in this research are students class X  SMAN 2 Karanganyar semester I  academic year  2011/2012.  Sample in this research are 2 class there are class X2 as control class and class X4 as experiment class. Technique of  data collection  test, questionnaire and observation sheet. Test is used to measure of cognitif domain and student creativity level, questionnaire is used to measure of afective domain, and observation sheet is used to measure of psikomotoric domain. Technique of data analysis use two ways Varians Analysis (ANAVA) and continuation test use double comparation Scheffe method. Based the result of this research can conclude are, (1) there is significant influence using learning model Group Investigation  towards the results study of Biology, (2) there is significant influence creativity level students towards the results study of Biology, (3) there is no interaction of significant influence?s between Group Investigation   model and creativity level  towards the results study of Biology. The result of continuation test use  Scheffe  method  can conclude are,  (1)  there is significant influence between  column  A1  (using  Group Investigation  model)  and  column  A2 (using Conventional model)  towards the results study of Biology, and (2) there is significant influence between row B1  (high level creativity) and  row B2  (low level creativity)  towards the results study of Biology. The case must be concern in implementation of learning model Group Investigation  for research to be effective are students psychological factors like as readiness students capability to learning be autonomous and the students anxienty with sub topic for investigated.   Keywords: Group Investigation, Creativity, Result Study of Biologi